The protective role of phlorizin against lipopolysaccharide-induced acute orchitis in mice associated with changes in gut microbiota composition - Guo, Qing; Li, Tian-Feng; Huang, Jiang; Li, Jing-Chun; Zhang, Ze-Cai; Qu, Yong-Li (Frontiers in Veterinary Science, 2024)
Objective: Orchitis is a common reproductive disease of male animals, which has serious harm implications to human and animal reproduction. Additionally, phlorizin (PHN), a common polyphenol in apples and strawberries, has a variety of biological activities, including antioxidant, anti-inflammatory, anti-diabetic, and anti-aging activities. We aimed to determine the protective effects and potential mechanisms of PHN in lipopolysaccharide (LPS)-induced acute orchitis in mice.Method: After 21 days of PHN pretreatment, mice were injected with LPS to induce testicular inflammation, and then the changes of testicular tissue structure, expression of inflammatory factors, testosterone level, expression of testosterone-related genes, adhesion gene and protein expression were detected, and the structural changes of in the intestinal flora after PHN treatment were further detected by 16SRNA.Result: Our results demonstrated that PHN treatment reduced LPS-induced testicular injury and body and testicular weight losses. The mRNA expression levels of pro-inflammatory cytokines-related genes and antioxidant enzyme activity were also decreased and elevated, respectively, by PHN administration; however, PHN treatment also reduced the LPS-induced decrease in testosterone levels in the testes. Additionally, further studies found that PHN increased the expression of marker proteins zonula occludens-1 (ZO-1) and occludin associated with the blood testosterone barrier compared with that in LPS treatment groups. To further examine the potential mechanisms of the protective effect of PHN on LPS-induced testicular injury, we compared the differences of gut microbiota compositions between the 100 mg/kg PHN treatment group and the control group using 16SRNA. Metagenomic 3 analyses indicated that the abundances of Bacteroidetes, Muribaculaceae, Lactobacillaceae, uncultured bacterium f Muribaculaceae, and Lactobacillus in the PHN treatment group improved, while potential microbes that can induce intestinal diseases, including Verrucomicrobia, Epsilonbacteraeota, Akkermansiaceae, and Akkermansia, decreased in the PHN treatment group.Our results indicate that PHN pretreatment might alleviate orchitis by altering the composition of gut microflora, which may provide a reference for reducing the occurrence of acute orchitis in male animals.